Analisis Mutu Kinerja Guru dalam Pelaksanaan Tugas sebagai Penanggung Jawab Program Sekolah: Kajian Literatur Berbasis Fenomena Lapangan - Ine Rahayu Purnamaningsih; Linayati Inayah; Khoiruddin Khoiruddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the quality of teacher performance in carrying out their duties as program coordinators in schools, identify influencing factors, and examine the effectiveness of a collaborative approach through the co-PJ tandem system as an alternative solution. The study uses a qualitative approach with a descriptive-analytical design through literature review enriched with empirical field phenomena. Data were collected through documentation techniques from various relevant scientific literatures and analyzed using content analysis with a thematic approach. The results show that the quality of teacher performance as program coordinators is still suboptimal, characterized by low understanding of roles, weak program planning and management, lack of coordination, and low independence in decision-making. These problems are influenced by various factors, including low work motivation, limited competence, insufficient teacher empowerment, high workload, weak supervision, and the absence of a collaborative work system. Furthermore, this study finds that the implementation of the co-PJ tandem system has a positive impact on improving teacher performance quality through strengthening collaboration, increasing self-confidence, improving program planning and implementation quality, and fostering innovation. In conclusion, improving teacher performance quality requires a systemic and collaborative approach. The co-PJ tandem system can be an innovative and effective model for strengthening teacher performance and supporting sustainable educational quality improvement.